Cardiac valve involvement in ADAR-related type I interferonopathy. Issue 7 (26th November 2019) - Crow, Yanick; Keshavan, Nandaki; Barbet, Jacques Patrick; Bercu, Geanina; Bondet, Vincent; Boussard, Charlotte; Dedieu, Nathalie; Duffy, Darragh; Hully, Marie; Giardini, Alessandro; Gitiaux, Cyril; Rice, Gillian Inara; et al.
Abstract : Background: Adenosine deaminases acting on RNA ( ADAR ) mutations cause a spectrum of neurological phenotypes ranging from severe encephalopathy (Aicardi-Goutières syndrome) to isolated spastic paraplegia and are associated with enhanced type I interferon signalling. In children, non-neurological involvement in the type I interferonopathies includes autoimmune and rheumatological phenomena, with calcifying cardiac valve disease only previously reported in the context of MDA5 gain-of-function. Results: We describe three patients with biallelic ADAR mutations who developed calcifying cardiac valvular disease in late childhood (9.5–14 years). Echocardiography revealed progressive calcification of the valvular leaflets resulting in valvular stenosis and incompetence. Two patients became symptomatic with biventricular failure after 5–6.5 years. In one case, disease progressed to severe cardiac failure despite maximal medical management, with death occurring at 17 years. Another child received mechanical mitral and aortic valve replacement at 16 years with good postoperative outcome. Histological examination of the affected valves showed fibrosis and calcification. Conclusions: Type I interferonopathies of differing genetic aetiology demonstrate an overlapping phenotypic spectrum which includes calcifying cardiac valvular disease. Individuals with ADAR -related type I interferonopathy may develop childhood-onset multivalvular stenosis and incompetence which can progress insidiously to symptomatic, and ultimately fatal, cardiac failure. Regular surveillance echocardiograms are recommended to detect valvular disease early.